2020
DOI: 10.1016/j.molcel.2019.10.028
|View full text |Cite
|
Sign up to set email alerts
|

A Non-amyloid Prion Particle that Activates a Heritable Gene Expression Program

Abstract: Highlights d The Vts1 IDR promotes its condensation into the non-amyloid prion [SMAUG + ] d [SMAUG + ] hyperactivates Vts1 function d [SMAUG + ] rewires post-transcriptional gene regulation to promote proliferation d Self-assembly is conserved in the human Vts1 homolog hSmaug1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 141 publications
2
62
0
Order By: Relevance
“…Confirming their presence would indicate their existence in all three domains of life, suggesting that prions were likely present during the time of LUCA. Though many prions do not form amyloid (73)(74)(75), in the current study we focused on amyloidforming cPrDs because recently identified bacterial prions have been shown to form amyloids (45), and amyloid fibril formation can also be detected with a relatively high-throughput experimental survey like the Congo red assay used here. We utilized the computational program PLAAC (49) to identify novel cPrDs.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming their presence would indicate their existence in all three domains of life, suggesting that prions were likely present during the time of LUCA. Though many prions do not form amyloid (73)(74)(75), in the current study we focused on amyloidforming cPrDs because recently identified bacterial prions have been shown to form amyloids (45), and amyloid fibril formation can also be detected with a relatively high-throughput experimental survey like the Congo red assay used here. We utilized the computational program PLAAC (49) to identify novel cPrDs.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Smaug orthologues as post-transcriptional regulators of energetic metabolism appears evolutionary conserved as yeast Vts1p –which forms MLOs and prion-like condensates– controls mRNAs linked to nutrient sensing (Chakravarty et al, 2020; She et al, 2017). Translation of nuclear-encoded transcripts at the mitochondrial periphery is known to be regulated by a reduced number of RNA-binding proteins, including the highly conserved factors clustered mitochondria homolog (CLUH) and Pumilio orthologs (reviewed in(D’Amico et al, 2019; Gao et al, 2014; Gehrke et al, 2015; Kopp et al, 2019; Lee & Tu, 2015; Olivas & Parker, 2000; Pla-Martin et al, 2020; Schatton et al, 2017; Schatton & Rugarli, 2018; Vardi-Oknin & Arava, 2019; Wakim et al, 2017) The putative interplay between these pathways and Smaug remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular consequences of Smaug-body formation are incipiently described. Condensation of the yeast ortholog Vts1 facilitates the degradation of target mRNAs (Chakravarty et al, 2020), whereas mammalian Smaug1-body dissolution is linked to mRNA release and translational activation of dendritic mRNAs (Baez et al, 2011; Luchelli et al, 2015). The formation of MLOs and related molecular condensates is thought to involve liquid-liquid phase separation (LLPS) processes driven by multiple protein-protein interactions, which remain unknown in the case of Smaug (Courchaine et al, 2016; Guo & Shorter, 2015; Perez-Pepe et al, 2018; Sachdev et al, 2019; Van Treeck et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of prion [␤] argues for omitting the amyloid formation from the list of essential properties of a prion. Two other recently described yeast prions, [SMAUGϩ], the product of the Vts1 gene, and [ESIϩ], the product of the Snt1 gene, also do not appear to form amyloids, though both may form other kinds of aggregates (26,27).…”
mentioning
confidence: 99%